Use of radiography in small animal practice in the UK and Republic of Ireland in 2013 - Booth, N.J.; Morley, S.J.; Ewers, Richard (BMJ Publishing Group, 2018)
Background: Radiography is an essential diagnostic tool in small animal practice. A major transition is currently underway from film-screen to digital systems. However, there is limited published research detailing the use of radiography in practices in the UK and Republic of Ireland (ROI). Aim: To describe the uptake of digital radiographic systems, wider aspects of radiographic practice and use of other diagnostic imaging techniques in the UK and ROI. Design: A cross-sectional study using paper and online questionnaires. Participants: Veterinary surgeons, veterinary nurses and veterinary radiographers working in small animal practice in the UK and ROI were eligible to participate in the survey. Results: Seventy-five per cent of respondents worked in practices using digital radiography systems. Cost appeared to be the largest barrier to digital conversion. Chemical restraint was used on 86% of cases, however 3% of cases were reported to be restrained by hand. Thirty-one percent of respondents had not received specific training in radiation safety. Ultrasonography was reportedly now widely utilised on a regular basis. Conclusions: These results provide useful information on the use of radiography and additional diagnostic imaging techniques in the UK. These results should be used to indicate future training requirements, particularly to improve radiation safety.